KERUKUNAN ANTARA JEMAAT GEREJA KRISTEN JAWA (GKJ) SLAWI DENGAN MASYARAKAT MUSLIM DI DESA BALAPULANG KULON KABUPATEN TEGAL - Christian Putra, Galih Mahardika (Faculty of Social Science, Universitas Negeri Semarang, 2015)
There is a harmony formed between congregations in BalapulangKulon village. This article intends to study a form of harmony and socio-cultural factors that influence the occurrence of the harmony. This study uses qualitative methods. Location of the study wasBalapulangKulon village, Tegal regency. Subjects were resident congregations and local Muslims. Research informants are boards of Gereja Kristen Jawa (Javanese Christian Church) Slawi, Islamic religion leaders and village officials. Data collection techniques used is observation, interviews, and documentation. The validity of the data usessource triangulation techniques. Techniques of data analysis include data collection, data reduction, data presentation, and verification. Form of harmony between the Muslim and church congregations in BalapulangKulon village is a joint effort and deliberation. Socio-cultural factors are the same region of residence, kinship, tolerance, community performance position, economic interests, self-awareness, and education. Suggestion for BalapulangKulon village government should be able to provide the same rights in society for Muslims and Javanese Christian Church congregation in Slawi and eliminate domination efforts against Christianity who belong to minorities so that inter-religious harmony can be maintained.